Low rate of nonrelapse mortality in under-4-year-olds with ALL given chemotherapeutic conditioning for HSCT: a phase 3 FORUM study - Bader, Peter; Pötschger, Ulrike; Dalle, Jean-Hugues; Moser, Laura M; Balduzzi, Adriana; Ansari, Marc; Buechner, Jochen; Güngör, Tayfun; Ifversen, Marianne; Krivan, Gergely; Pichler, Herbert; Renard, Marleen; et al. (Blood advances, 2024)
Allogeneic hematopoietic stem cell transplantation (HSCT) is highly effective for treating pediatric high-risk or relapsed acute lymphoblastic leukemia (ALL). For young children, total body irradiation (TBI) is associated with severe late sequelae. In the FORUM study (NCT01949129), we assessed safety, event-free survival (EFS), and overall survival (OS) of 2 TBI-free conditioning regimens in children aged <4 years with ALL. Patients received fludarabine (Flu), thiotepa (Thio), and either busulfan (Bu) or treosulfan (Treo) before HSCT. From 2013 to 2021, 191 children received transplantation and were observed for ≥6 months (median follow-up: 3 years). The 3-year OS was 0.63 (95% confidence interval [95% CI], 0.52-0.72) and 0.76 (95% CI, 0.64-0.84) for Flu/Thio/Bu and Flu/Thio/Treo (P = .075), respectively. Three-year EFS was 0.52 (95% CI, 0.41-0.61) and 0.51 (95% CI, 0.39-0.62), respectively (P = .794). Cumulative incidence of nonrelapse mortality (NRM) and relapse at 3 years were 0.06 (95% CI, 0.02-0.12) vs 0.03 (95% CI: <0.01-0.09) (P = .406) and 0.42 (95% CI, 0.31-0.52) vs 0.45 (95% CI, 0.34-0.56) (P = .920), respectively. Grade >1 acute graft-versus-host disease (GVHD) occurred in 29% of patients receiving Flu/Thio/Bu and 17% of those receiving Flu/Thio/Treo (P = .049), whereas grade 3/4 occurred in 10% and 9%, respectively (P = .813). The 3-year incidence of chronic GVHD was 0.07 (95% CI, 0.03-0.13) vs 0.05 (95% CI, 0.02-0.11), respectively (P = .518). In conclusion, both chemotherapeutic conditioning regimens were well tolerated and NRM was low. However, relapse was the major cause of treatment failure. This trial was registered at www.clinicaltrials.gov as #NCT01949129.
Keywords: recidiva; transplantace hematopoetických kmenových buněk; busulfan; Humans; dítě; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Child; thiotepa; příprava pacienta k transplantaci; lidé; předškolní dítě; nemoc štěpu proti hostiteli; Transplantation Conditioning; Thiotepa; Recurrence; Busulfan; akutní lymfatická leukemie; Child, Preschool; Precursor Cell Lymphoblastic Leukemia-Lymphoma